1251 FRAILTY PREVALENCE AND RISK OF SARCOPENIA IN OLDER HEART FAILURE (HF) INPATIENTS. (16th January 2023) - Obiechina, N; Michael, A; Gill, A; Carey, P; Shah, G; Nehikhare, I; Khan, R; Slavica, M; Khan, T; Rahman, S; Mushtaq, W; Brar, H; et al.
Abstract: Introduction: Both frailty and HF are common in the elderly population. Elderly HF patients have an increased risk of frailty and elderly frail patients are at a higher risk of developing HF. Frailty is an independent predictor of mortality in cardiovascular disease. Sarcopenia (defined as decreased muscle mass and muscle strength and/or performance) is also prevalent in HF patients and may progress to cardiac cachexia. HF may induce sarcopenia and sarcopenia may contribute to the poor prognosis of HF. Aims: To assess the prevalence of frailty in older HF inpatients To determine the risk of sarcopenia in these patients Methods: A cross-sectional, retrospective analysis of consecutive patients, 60 years and over, admitted with HF to a UK hospital. Data was manually extracted from anonymized electronic records. The Rockwood Clinical Frailty Scale (CFS) was used for assessment for frailty and the SARC-F tool was used for screening for sarcopenia. Patients with medical history of HF but did not present with decompensated HF were excluded. Also, patients with incomplete data were excluded. The IBM SPSS 28 statistical package was used for statistical analysis. Descriptive statistics and risk estimates were calculated. Results: 163 patients were analysed; 82 males and 81 females. The mean age was 81.4 years (SD 9.69). 71.5 % of patients were frail while 28.5 % were non-frail. The risk of sarcopenia was 10.9 times greater in the frail than in the non-frail patients (OR = 10.9; 95% C.I 4.85 – 24.67). There was a lower risk of sarcopenia in male patients than in the female patients (OR =0.45; 95% C.I 0.22 – 0.94). Conclusions: Frailty is prevalent in older heart failure inpatients. It significantly increases the risk of sarcopenia in these patients. Women are at higher risk of sarcopenia than men. More research is needed into frailty and sarcopenia in.